Climbing up the ladder and watching out for the fall: Poverty dynamics in rural Bangladesh - Ahmed, Akhter; Tauseef, Salauddin (University Press Limited, 2021)
In Bangladesh, the pace of economic growth accelerated in recent years, with real GDP growing at a rate of 6.5 percent on average per year between 2010 and 2016, reaching 7.3 percent in 2017—the highest in the country’s history. The incidence of poverty in Bangladesh was cut in half in the past 16 years, dropping from 48.9 percent in 2000 to 24.3 percent in 2016. In rural areas, poverty headcount declined from 52.3 percent to 26.4 percent over the same period (BBS 2017).